1990
DOI: 10.1161/01.hyp.15.2_suppl.i81
|View full text |Cite
|
Sign up to set email alerts
|

Dietary linoleic acid prevents the development of deoxycorticosterone acetate-salt hypertension.

Abstract: The aim of this study was to elucidate the effect of dietary variations of linoleic acid on the development of deoxycorticosterone acetate (DOCA)-salt hypertension in rats. All rats were divided into three groups and fed one of the following isocaloric diets with 8% NaCl: a high linoleic acid (HLA) (20% sunflower oil), a moderate linoleic acid (5% lard oil+15% sunflower oil), or a low linoleic acid (DLA) (20% lard oil). After 4 weeks of feeding, we determined intraerythrocyte sodium, potassium, and magnesium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
1
4
1
Order By: Relevance
“…In addition, the 1980 diet was higher in salt, and in the experi- mental studies in rats the BP response to dietary fat modification was most evident in animals with low baseline PUFA and high sodium intake. 2,3 The changes in the background diet between early 1980s and the 1990s in North Karelia have been similar to those found in all parts of Finland. 52 The total fat intake of the population has decreased due to reduced intake of SAFA, and the consumption of PUFA has increased concomitantly.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In addition, the 1980 diet was higher in salt, and in the experi- mental studies in rats the BP response to dietary fat modification was most evident in animals with low baseline PUFA and high sodium intake. 2,3 The changes in the background diet between early 1980s and the 1990s in North Karelia have been similar to those found in all parts of Finland. 52 The total fat intake of the population has decreased due to reduced intake of SAFA, and the consumption of PUFA has increased concomitantly.…”
Section: Discussionsupporting
confidence: 63%
“…2,3 In man the effects of dietary fat on BP have been extensively studied, but the results of both observational studies and intervention trials have been conflicting as summarised in several review articles. [4][5][6][7][8] Total fat intake has not been associated with BP in human cross-sectional studies.…”
Section: Introductionmentioning
confidence: 99%
“…The hypotensive effect of linoleic acid in deoxycorticosterone acetate-salt hypertension in rats was correlated with increases in the activity of the Na ϩ /K ϩ -ATPase pump. 15 Thus, it may be possible that linoleic acid, by increasing fluidity, activates the pump, which in turn alters the membrane potential of VSMC, causing vasodilation. Although arachidonic and linoleic acids have been reported to have an inhibitory effect on Na ϩ /K ϩ -ATPase, 38 unsaturated fatty acids have recently been shown to activate the Na ϩ /K ϩ -ATPase pump, while saturated fatty acids such as palmitic acid had little or no effect.…”
Section: Discussionmentioning
confidence: 99%
“…15 It has also been shown that gamma-linolenic acid, a metabolite of linoleic acid, attenuates stress-induced hypertension.…”
mentioning
confidence: 99%
See 1 more Smart Citation